2018
DOI: 10.1111/jir.12485
|View full text |Cite
|
Sign up to set email alerts
|

A descriptive analysis of self‐injury in community settings: exploring behaviour–behaviour contingencies

Abstract: Our results suggest the direction and strength of SIB-SIB contingencies may be fluid based on the presence or absence of certain environmental context variables. Evaluating SIB-SIB contingencies under different environmental conditions may help identify contexts in which SIB is likely to persist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…The three participants in this study engaged in frequent and sequentially dependent SIB across the majority of conditions and sessions. These results reproduce others’ results that have reported that for many individuals with SIB living in institutions and community settings, the best predictor of SIB is a previous instance of SIB (Courtemanche et al, 2018; Kemp et al, 2008; Marion et al, 2003; Sandman et al, 2008; Sandman, Touchette, Marion, Lenjavi, & Chicz-Demet, 2002).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The three participants in this study engaged in frequent and sequentially dependent SIB across the majority of conditions and sessions. These results reproduce others’ results that have reported that for many individuals with SIB living in institutions and community settings, the best predictor of SIB is a previous instance of SIB (Courtemanche et al, 2018; Kemp et al, 2008; Marion et al, 2003; Sandman et al, 2008; Sandman, Touchette, Marion, Lenjavi, & Chicz-Demet, 2002).…”
Section: Discussionsupporting
confidence: 91%
“…For each participant, we obtained total frequencies of SIB for each session, which were then converted to a rate measure by dividing the total number of instances of SIB during each session by the duration of the session. We also used an event lag with pauses method of sequential analysis (Lloyd, Yoder, Tapp, & Staubitz, 2016) to estimate SIB–SIB contingencies for each session as described in Courtemanche et al (2018). For each session, in the MOOSES file, 10-s pause events were inserted to represent 10-s periods in which no SIB occurred.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations